Wideband Over-the-Air RF Self-Interference Cancellation by an EML-Based Optical System With Baseband Predistortion - Yunhao Zhang; Longsheng Li; Shilin Xiao; Meihua Bi; Yinghong Yu; Weisheng Hu (IEEE Photonics Journal)
In this paper, we propose and experimentally demonstrate an optical self-interference cancellation (OSIC) system with baseband predistortion for wideband over-the-air in-band full-duplex (IBFD) communication. The key factors of OSIC bandwidth limitation are analyzed, and the solution toward it is proposed for the first time. Experimental results show that, by traditional OSIC under over-the-air condition, only narrow even zero band is with enough cancellation depth to satisfy IBFD. But with our proposed baseband predistortion scheme, deep OSIC depth is achieved over the whole 1 GHz/5 GHz baseband within the total 7–25 GHz available band of horn antennas. The employment of baseband predistortion obviously broadens the cancellation bandwidth of an EML-based OSIC system. The largest OSIC bandwidth for over-the-air IBFD communication is demonstrated so far.